2021
DOI: 10.1002/jcla.24015
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the HOXA gene family and its relationship to prognosis and immune infiltrates in cervical cancer

Abstract: Cancer has been the leading cause of death worldwide. Cervical cancer is the most common gynecological malignancy, the third most common malignant tumor in women worldwide, and the most common malignant tumor among Chinese women. According to a statistical report, a total of 65,620 patients were newly diagnosed with cervical cancer in 2020. 1 The largest preventable cancer contributor in China is chronic infection, which is responsible for approximately 17% of all cancers in China 2 and is predominantly compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…On chromosome 7, we found candidate genes belonging to the HOXA-family that exhibit high sweep support with 11-window mean sweep probabilities ranging from 0.80 to 0.95 (Figure S10H). HOXA genes are part of the homeobox cluster, which encode proteins that play an important part in early development of humans by performing embryo segmentation [Shah N, 2010], and it has been suggested that HOXA-family genes are involved in the inception and development of human cancers [Ge et al, 2021]. Specifically, HOXA9 (Figure S10H) is responsible for the pathogenesis of acute myelogenous leukemia, which is a cancer of the bloods and bones [Chen et al, 2019].…”
Section: Resultsmentioning
confidence: 99%
“…On chromosome 7, we found candidate genes belonging to the HOXA-family that exhibit high sweep support with 11-window mean sweep probabilities ranging from 0.80 to 0.95 (Figure S10H). HOXA genes are part of the homeobox cluster, which encode proteins that play an important part in early development of humans by performing embryo segmentation [Shah N, 2010], and it has been suggested that HOXA-family genes are involved in the inception and development of human cancers [Ge et al, 2021]. Specifically, HOXA9 (Figure S10H) is responsible for the pathogenesis of acute myelogenous leukemia, which is a cancer of the bloods and bones [Chen et al, 2019].…”
Section: Resultsmentioning
confidence: 99%
“…S17H , Supplementary Material online). HOXA genes are part of the homeobox cluster, which encode proteins that play an important part in early development of humans by performing embryo segmentation ( Shah and Sukumar 2010 ), and it has been suggested that HOXA-family genes are involved in the inception and development of human cancers ( Ge et al 2021 ). Specifically, HOXA9 (supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%